Molecular dynamics of three different α-helices in ribosomal protein L25 from Escherichia coli - Yuri Chirgadze; Ilya Likhachev; Nikolai Balabaev; Evgeniy Brazhnikov (Biochemistry and Biophysics Reports, 2024)
A true native protein state is realized in a water solution where proteins exhibit their dynamic properties important for the functioning. This is way we have analyzed the dynamics of α-helices inside ribosomal protein L25 from Escherichia coli in a water solution. The dynamics of only main chain Cα-atoms have been simulated along the five independent trajectories at a total time 200ns. Superposed average dynamics picture of L25 structure coincides very well with the NMR protein structure in a water solution. Dynamic shifts of Cα-atoms of the α-helices are related with a restraint status of the residue side chain. In contrast, Cα-atoms of the β-sheet, which form a hydrophobic core, show very low dynamic motion and higher stability. Dynamic specificity of the main chain of protein L25 could explain its particular features in the complex with 5S rRNA and in the structure of the ribosome.